(untitled) - McDonnell, Philip J. (Hoboken, N.J., 2008)
Optimal Portfolio Modeling is an easily accessible introduction to portfolio modeling for those who prefer an intuitive approach to this discipline. While early chapters provide engaging insights on the statistical properties of markets, this book quickly moves on to illustrate invaluable trading and risk control models based on popular programs such as Excel and the statistical modeling language R. This reliable resource presents modeling formulas that will allow you to effectively maximize the performance, minimize the drawdown, and manage the risk of your portfolio.
Keywords: Portfolio management,Risk management,Investments,Quản lý danh mục đầu tư,Quản lý rủi ro,Khoản đầu tư